Factors affecting chemistry learning achievement and the most effective methods for lecturers to help students improve their understanding and marks, Faculty of Education, Souphanouvong University - YONGYE, Noulongxiong; LAMPHAIPHANH, Ketsalinh; SOURVATHAO, Vixai; YIAMACHANG, Suechang; CHOUALUEHER, Sivone; VANDALAK, Phonesavanh; KONEPACHITH , Domone; PHIPHATPHON, Soudavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
The purpose of this study was to determine which factors had positive or negative effects on Year1 chemistry students’ marks and understanding, and to ask for suggestions for ways to improve their learning. The factors examined included students’ reasons for selecting to study chemistry, background prior to attending university, and background, situational and societal attitudes toward chemistry. There were 25 chemistry students in the Year 1 population in academic year 2016-2017, and they were surveyed in October 2018. The rate of return for the questionnaire was 100 per cent. Students’ reasons for selecting to study chemistry showed that 56% were influenced by their parents, while 44% expected to get good jobs in the future. With respect to students’ backgrounds prior to attending university, 52% came from poor families. Studying chemistry was the first choice for 52% and the second choice for 36%. Most students (76%) had never done experiments in high school. With respect to attitudinal factors, only 20% of students liked chemistry best in high school though 44% had had good chemistry learning results, only 8% believed that chemistry was easy, 40% used their phones and computers to help them study, and 80% thought that government and industry would need more chemists in the next 5 year. The students’ biggest challenge in learning chemistry was that 68% thought they had inadequate chemistry backgrounds. Suggestions for improving learning were that 60% of students thought they needed to do practical experiments and watch more teacher demonstrations, while 52% required extra classes to improve their basic chemistry.